2014
DOI: 10.1371/journal.pone.0098120
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Characterization of a Thailand–Myanmar Isolate, MS6, of Vibrio cholerae O1 El Tor, Which Is Phylogenetically Related to a “US Gulf Coast” Clone

Abstract: BackgroundThe cholera outbreaks in Thailand during 2007–2010 were exclusively caused by the Vibrio cholerae O1 El Tor variant carrying the cholera toxin gene of the classical biotype. We previously isolated a V. cholerae O1 El Tor strain from a patient with diarrhea and designated it MS6. Multilocus sequence-typing analysis revealed that MS6 is most closely related to the U. S. Gulf Coast clone with the exception of two novel housekeeping genes.Methodology/Principal FindingsThe nucleotide sequence of the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…First, 70% of L3b isolates carried the quinolone resistance gene qnrS, with an even higher proportion of 83% among Hangzhou isolates (Fig 1B). qnrS was first reported in isolate MS6 from Thailand [55] (L3b.4), located in the superintegron region, which functions as a gene capture system with gene content varying considerably among V. cholerae isolates. Outside of the L3b and L9 lineages, the gene was only found in 4% isolates.…”
Section: Virulence Factors Antimicrobial Resistance and Unique Genommentioning
confidence: 99%
See 1 more Smart Citation
“…First, 70% of L3b isolates carried the quinolone resistance gene qnrS, with an even higher proportion of 83% among Hangzhou isolates (Fig 1B). qnrS was first reported in isolate MS6 from Thailand [55] (L3b.4), located in the superintegron region, which functions as a gene capture system with gene content varying considerably among V. cholerae isolates. Outside of the L3b and L9 lineages, the gene was only found in 4% isolates.…”
Section: Virulence Factors Antimicrobial Resistance and Unique Genommentioning
confidence: 99%
“…In addition to the Hangzhou isolates, there were 46 L3b and L9 isolates from Turkmenistan, Russia, Ukraine, Thailand, Mexico, Haiti, Argentina and Paraguay (Fig 1B and 1C and S9, S1 Table). They were isolated from patients (48%) or environment (52%, water and food) from 1965 to 2015, during the diarrheal/cholera outbreaks or by routine surveillance [8,17,18,[23][24][25]55] (S1 Table and S7B Fig). Due to the usually mild symptoms of human infection caused by these two lineages, their sampling is limited compared to the pandemic lineage, which can affect the inference of the routes and directions of spread.…”
Section: Evidence For the Global Spread Of L3b And L9 Lineagesmentioning
confidence: 99%
“…To date, more than 30 complete and numerous draft genome sequences for V. cholerae strains are available in the Gen-Bank database (http://www.ncbi.nlm.nih.gov/genom e/) or online (http://www.genom esonl ine.org). Many comparative analyses of these V. cholerae genomes have been reported (e.g., Banerjee et al 2014;Dutilh et al 2014;Okada et al 2014;Garrine et al 2017;Imamura et al 2017). In the present study, we determined the complete genome sequence of V. cholerae CHN108B (non-O1/O139 serogroup, ct − tcp − ), which was recently isolated from surface water from the Yangtze River Estuary, China (Song et al 2013), to address the lack of complete genome data regarding this bacterium originating from an estuary environment in China (Yi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…b). Blast search revealed that two ORFs at the 5′‐end, ET1_207 and ET1_192; and three ORFs at the 3′‐end, ET1_279, ET1_351, and ET1_222, are homologous to the corresponding ORFs of MS6CTXAGI prophage with 99%–100% identities, and also to those of “novel hybrid RS1” with 97%–99% identities. In addition, the ORF ET1_222 is a homologue of rstC of strain N16961 with amino acid substitutions from Asp to Ser at position 54, and from Gly to Lys at 67.…”
Section: Resultsmentioning
confidence: 99%
“…A maximum‐likelihood phylogenetic tree of 32 V. cholerae strains was constructed based on SNP differences across 2483 core genes, excluding likely recombination events, with RAxML 8.2.4 with 1000 bootstrap replicates. Of the 18 strains analyzed in the study, 14 were composed of two strains of wave 1 (N16961, RC9), four were wave 2 (MO10, VC51, B33, MJ1236) and four wave 3 (4675, CIRS101, 2010EL1786, 4679) of the seventh cholera pandemic, three were pre‐seventh pandemic (M66‐2, MAK757, C5), and MS6, a reported “US Gulf Coast” strain was also included (Table ). The whole genome core genes were identified using conserved gene neighborhood information implemented in Roary.…”
Section: Methodsmentioning
confidence: 99%